C. elegans VWA-8 is a mitochondrial protein - Zhu, Ming; Chisholm, Andrew D; Jin, Yishi (microPublication Biology, 2020)
VWA8 proteins, named for von Willebrand factor A (VWA) domain containing 8, are conserved from worm to mammals (Whittaker & Hynes, 2002). In mouse, vwa8 gene produces long and short protein isoforms (VWA8a and VWA8b), and in rat livers VWA8a has been shown to localize to the matrix side of inner mitochondrial membrane (Luo et al., 2020). C. elegans vwa-8 is also predicted to produce two major protein isoforms. The short isoform (974 AA) shares identical AA sequences as the long isoform (1804 AA). The two isoforms contain an MTS (mitochondrial targeting sequence) at the N terminus, followed by three AAA ATPase domains, which are associated with diverse cellular activities; and the long isoform contains a VWA domain at the C terminus. To determine the endogenous expression pattern of C. elegans VWA-8, we generated a GFP knock-in allele, ju1799, in which GFP was in-frame fused at the C terminus to label the full-length protein specifically. The endogenous VWA-8::GFP was expressed in mitochondria of hypodermis, intestine and muscle, but was not detectable in neurons (Fig 1A). In hypodermis, VWA-8::GFP was colocalized with MitoTracker Red, a mitochondria marker (Fig 1B).